POST-PRECAMBRIAN MAGMATISM IN EASTERN FINNMARK, NORWAY: MANTLE SOURCES, POSSIBLE ORIGINS AND DIAMOND POTENTIAL - Eriksen, Glenn Martin Dagsvold (UiT Norges arktiske universitet, 2013)
Mantle sources under the Eastern Finnmark Region (EFR) appears to have inherited small scale heterogeneity from Precambrian geodynamics. Compositions varying from depleted and slightly enriched (similar to N-MORB and E-MORB), to enriched (similar to OIB type), are present in the EFR. Geochemical trends also indicates that some mantle sources has been to some extent influenced by subducting sediments, likely from an Early Paleozoic convergent margin. Some of the mantle sources under Sør-Varanger area are geochemically similar to deep mantle sources capable of producing kimberlitic and related magmas, and indeed exotic and potentially diamondiferous rock suites has been identified and classified from the large number of samples collected during field work in Sør-Varanger area. This combined with previously documented ideal crustal and mantle conditions for diamond emplacement in the Fennoscandian Shield gives the Sør-Varanger region a very good diamond potential.